Performance of Fodder Beet in Oman - Nadaf, S K; Ibrahim, Y M; Akthar, M; Haj, M G.El; Al-Lawati, A H (Annals of Arid Zone, 2016)
Three fodder beet (Bera ,vulgaris var. Crassa) genotypes. viz. Peramono. Petra and Anissa. were evaluated for their productivity. feeding value and quality. during winter 1994-95 and 1995-96 at both Agriculture Research .Center (ARC) and Livestock Research Center (LRC) at Rumais. Sultanate of Oman. These three genotypes were not significantly different for yield and yield associaleu characters at both the locations. The yield of fodder beet genotypes at ARC (94.62 to 110.88 t ha-1 and 136.41 to 151.08 t ha-1. respectively. during 1994-95 and 1995-96). having loamy sand soil with irrigation water of over 5000 m mhos cm-1. were more than those at LRC (72.90 to 79.34 t ha’i and 102.74 to 120.87 t ha-1 respectively. during 1994-95 and 1995-96) having loamy soil with irrigation water of about 2000 m mhos cm-1. Fodder beet tubers were nutritive and could be a good source of carbohydrates. It is recommended to chop beet tops and tubers as both intake and milk production were improved by chopping.